2021
DOI: 10.1016/j.pec.2021.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Deaf adults at higher risk for severe illness: COVID-19 information preference and perceived health consequences

Abstract: Objectives This study explores deaf and hard of hearing (DHH) individuals’ preferred sources of information for COVID-19 and their perceptions of developing severe illness from COVID-19 given underlying medical conditions. Methods A national online bilingual American Sign Language/English survey was conducted from April 17 to May 1, 2020. Weighted sample of 474 DHH adults living in the United States. Multivariate logistic regression analyses were conducted to examine in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…Deaf individuals typically experience challenges in acquiring health information, resulting in substantial disparities in health knowledge and discrepancies in preventative health care [ 19 ], and this gap has increased during the COVID-19 epidemic. For example, in the beginning of the epidemic, the sign language related to COVID-19 was inadequately established, resulting in misinformation and confusion [ 20 ]. As the media started intensively focusing on the virus, the World Health Organization (WHO) failed to deliver a conventional sign for COVID-19, leaving this responsibility to deaf communities.…”
Section: Related Workmentioning
confidence: 99%
“…Deaf individuals typically experience challenges in acquiring health information, resulting in substantial disparities in health knowledge and discrepancies in preventative health care [ 19 ], and this gap has increased during the COVID-19 epidemic. For example, in the beginning of the epidemic, the sign language related to COVID-19 was inadequately established, resulting in misinformation and confusion [ 20 ]. As the media started intensively focusing on the virus, the World Health Organization (WHO) failed to deliver a conventional sign for COVID-19, leaving this responsibility to deaf communities.…”
Section: Related Workmentioning
confidence: 99%
“…On the other hand, an inclusive society is created when every member of the community is accepted on an equal footing, when everyone has the opportunity to participate in the labor market and employment processes, access education, social services and fully function in everyday life (Dwyer et al, 2019;Moriña et al, 2020;Hall et al, 2019). Paradigms of policy and practice, characterized by both cultural and equal opportunities, shape the processes of reducing social exclusion through the satisfaction of individual needs (Blanck, 2020).…”
Section: Inclusive Society: a Context Of The Researchmentioning
confidence: 99%
“…Recent studies showed that older DHH people may suffer exponentially more physical and mental effects during the COVID-19 pandemic when both hearing impairment and old age are present [ 9 ], some of whom often encounter information, communication and healthcare barriers [ 10 , 11 ]. These populations could be more vulnerable than hearing older adults [ 12 ]. As a matter of fact, older individuals with hearing loss have a higher chance of having chronic conditions such as stroke, diabetes, hypertension and asthma [ 13 ], with a high prevalence of some chronic conditions, this population is more likely to visit hospitals or emergency departments during a COVID pandemic, where has a higher likelihood of being exposed to COVID-19 infection [ 9 , 14 ].…”
Section: Introductionmentioning
confidence: 99%